Transplantation of Autologous Olfactory Ensheathing Cells in Complete Human Spinal Cord Injury - Tabakow, Pawel; Jarmundowicz, Wlodzimierz; Czapiga, Bogdan; Fortuna, Wojciech; Miedzybrodzki, Ryszard; Czyz, Marcin; Huber, Juliusz; Szarek, Dariusz; Okurowski, Stefan; Szewczyk, Pawel; Gorski, Andrzej; Raisman, Geoffrey (Cell transplantation, 2013)
Numerous studies in animals have shown the unique property of olfactory ensheathing cells to stimulate regeneration of lesioned axons in the spinal cord. In a Phase I clinical trial, we assessed the safety and feasibility of transplantation of autologous mucosal olfactory ensheathing cells and olfactory nerve fibroblasts in patients with complete spinal cord injury. Six patients with chronic thoracic paraplegia (American Spinal Injury Association class A-ASIA A) were enrolled for the study. Three patients were operated, and three served as a control group. The trial protocol consisted of pre- and postoperative neurorehabilitation, olfactory mucosal biopsy, culture of olfactory ensheathing cells, and intraspinal cell grafting. Patient's clinical state was evaluated by clinical, neurophysiological, and radiological tests. There were no adverse findings related to olfactory mucosa biopsy or transplantation of olfactory ensheathing cells at 1 year after surgery. There was no evidence of neurological deterioration, neuropathic pain, neuroinfection, or tumorigenesis. In one cell-grafted patient, an asymptomatic syringomyelia was observed. Neurological improvement was observed only in transplant recipients. The first two operated patients improved from ASIA A to ASIA C and ASIA B. Diffusion tensor imaging showed restitution of continuity of some white matter tracts throughout the focus of spinal cord injury in these patients. The third operated patient, although remaining ASIA A, showed improved motor and sensory function of the first spinal cords segments below the level of injury. Neurophysiological examinations showed improvement in spinal cord transmission and activity of lower extremity muscles in surgically treated patients but not in patients receiving only neurorehabilitation. Observations at 1 year indicate that the obtaining, culture, and intraspinal transplantation of autologous olfactory ensheathing cells were safe and feasible. The significance of the neurological improvement in the transplant recipients and the extent to which the cell transplants contributed to it will require larger numbers of patients.